Applied history and the teaching of leadership: a case for the use of historical case studies in leadership programs - von Feigenblatt, Otto Federico; Linstroth, J. P. (Universidad y Sociedad, 2022)
Macro level theories and a vast array of “best practices” characterize leadership training programs. Nevertheless, the importance of concrete case studies has been proven in business education and a small yet growing number of historians are focusing on the application of historical studies to contemporary problems. The present study explores a few successful initiatives in the inchoate field of applied history and provides a few suggestions as to how applied history can enrich the teaching of leadership in a vast array of programs ranging from business administration to educational leadership. Additionally, and specifically, historical leadership in relation to courage is discussed, thereby demonstrating why history is so crucial and as exemplar for the epistemology of leadership in education. Keywords: Applied History, Courage, Leadership, Teaching, Training. RESUMEN Los programas de formación en liderazgo se caracterizan por sus teorías a nivel macro y una amplia gama de "mejores prácticas". Sin embargo, la importancia de los estudios de casos concretos ha quedado demostrada en la educación empresarial y un número pequeño pero creciente de historiadores se está centrando en la aplicación de los estudios históricos a los problemas contemporáneos. El presente estudio explora algunas iniciativas exitosas en el incipiente campo de la historia aplicada y ofrece algunas sugerencias sobre cómo la historia aplicada puede enriquecer la enseñanza del liderazgo en una amplia gama de programas que van desde la administración de empresas hasta el liderazgo educativo. Además, y de forma específica, se analiza el liderazgo histórico en relación con el valor, demostrando así por qué la historia es tan crucial y como ejemplo para la epistemología del liderazgo en la educación. Palabras clave: Historia aplicada, Valor, Liderazgo, Enseñanza, Formación